Creating Product Profile Website For Jersey Online Figures: Pembuatan Website Product Profil Tokoh Jersey Online - Rusminudi, Muhammad Rifaldi; Cindy Taurusta (Universitas Muhammadiyah Sidoarjo, 2024)
In the current digital era, websites have become an important means of promoting products to potential consumers. Online jersey figures are a product that is popular among sports fans. This product usually displays pictures or names of sports figures admired by fans. This research aims to develop a product profile website which is an important means of promoting products to potential consumers. A product profile website is a website that displays information about the products offered by a company. This website usually contains information about product specifications, prices, how to order, and other features. An effective product profile website can help companies increase product sales. This research also aims to prove that product profile websites are created using The waterfall method is suitable for creating websites with basic features because this method is easy to understand and apply. These elements can be text, images, videos and other elements. Which can be an effective means of promoting products. This evidence will be obtained by conducting research that measures the effectiveness of product profile websites in increasing product sales. The results of this research show that product profile websites created using the Waterfall method are more effective in attracting the attention of potential consumers and encouraging them to take action, such as buying a product.